Management of social tension: Rethinking on politico-administrative response - Mukhopadhyay, Asok (2002)
The tensions may erupt in societies abruptly and unplanned, yet the response system to anticipate and contain social tension has to be thoughtfully and meticulously planned. The author has listed various grounds and factors which contribute towards social strife and ugly conflicts. However, he maintains that most of these situations can be managed by an honest, apolitical and reasoned approach. The fast and quick strides in the field of education, science, technology and communications provide us enough strength to ward off social tension, whether it is born out of traditional factors like caste and communalism or modern day perils of globalisation and cultural invasion. - Reproduced.
Keywords: Social conflicts